Kearifan Lokal: Moderasi Beragama Dan Budaya Patriarki Dalam Sebuah Pertentangan Perspektif Hak Asasi Manusia - Oktavriana, Diah Ratri; Nasiri, Nasiri; Yamani, Yamani; Achmad, Achmad (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
This research aims to find out how various moderation indicators are implemented regarding the community's cultural acceptance of the application of patriarchal culture and what form of government protection there is against acts of violence against women due to the application of patriarchal culture from a Human Rights perspective. Through normative research methodology, the research results show that Islam is a religion that is rahmatan lil'alamin which will not give a negative stigma to men or women. Thus, the position of men and women in Islam is the same. After marriage, the wife's responsibility will shift to the husband and this is a respect given by Islam to a woman. Apart from that, it was also explained that the best Muslim man is one who treats his wife well. Of course, this will get better if it is accompanied by an understanding of the concept of good religious moderation. Because no matter what, culture will continue to follow the flow of habits that have been adopted by society. However, the existence of moderate religion can save the life of the nation and state. Apart from that, it is further regulated in Article 27 paragraph (1) of the 1945 Constitution of the Republic of Indonesia, that Indonesia recognizes the principle of equality. This principle of equality applies to all Indonesian people. Recognition of the principle of equality in the Indonesian constitution leads to the elimination of discrimination, therefore, whoever we are as long as we are Indonesian citizens have the right to receive equal treatment before the law. Equal treatment before the law does not look at a person's ethnicity, religion, gender or even position. This indicates that Indonesia as a sovereign country legally recognizes the principle of equality. This means that according to legal instruments in statutory regulations, the position of men and women is equal. However, even though legal instruments are in place, in the context of implementing these legal instruments, discrimination and injustice towards women are often still visible.